The Development of Interactive Multimedia Using Smart Apps Creator Applications in Class VII Junior High School Informatics Subjects - Randhi Lasepdika Kasna; Syafril Syafril; Fetri Yeni J; Novrianti Novrianti (UMSU, 2023)
This research was motivated by challenges that are often faced by students, namely difficulty understanding the subject matter. This is due to several factors, such as the dominance of learning approaches that involve oral explanations from teachers in class, activities to record or summarize lessons, the material presented in teaching material books is only concise, and the lack of use of learning media-based teaching materials by teachers and schools. The purpose of this study is to create interactive multimedia based on appropriate development procedures, adhering to standards of validity and practicality criteria. Thus, the end goal is to produce interactive multimedia that can be considered appropriate for use in the learning process.Â The type and method of research used in this study is research and development (Research and Development-R D) by applying a 4-D model. The development process in this study consists of four stages, namely Define, Design, Development, and Disseminate). The evaluation of product validity is carried out through the participation of three experts, consisting of two validator experts in the media field and one validator expert in the material field. In addition, the product practicality test was carried out involving 16 students from grade VII of SMP Pertiwi 2 Padang. The results of this study showed that the evaluation of media validator experts was declared as